The value of parotid sialography in the diagnosis and staging of Sjogren's syndrome - Yutian Wang; Xiaoyan Xie; Ying Han; Xingyun Liu; Qianyun Guo; Lei Zhang; Xinyi Ni; Hongwei Liu (Elsevier, 2024)
Background/purpose: 2016 American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) primary Sjögren's syndrome (SS) diagnostic criteria did not incorporate radiographic examination while staging SS according to salivary gland imaging and serological autoantibody tests was not discussed. The aim is to study the value of parotid sialography for diagnosing SS, and to initially explore the method of staging SS based on the results of imaging and serological autoantibody tests. Materials and methods: 287 patients' clinical records were included. The sensitivity and specificity of parotid sialography in the diagnosis of SS were investigated. SS patients were categorized into early stage (autoantibody positive, imaging does not support SS), active stage (autoantibody positive, imaging supports SS), and quiescent stage (autoantibody negative, imaging supports SS), clinical characteristics of different stages were compared. Results: The sensitivity of parotid sialography for the diagnosis of SS was 82.6%, the specificity was 71.5%. 10-minute USFR of the patients in the active stage (0.18 ± 0.38 ml/10min) was significantly lower than that of early stage (0.34 ± 0.47 ml/10min) and quiescent stage (0.54 ± 0.52 ml/10min), P = 0.010, and the rate of confirmed SS was significantly higher in the active stage (82.9%) than that in the early stage (44.4%) and the quiescent stages (14.8%), P < 0.001. Conclusion: Parotid sialography remains valuable in the diagnosis of SS. Performing imaging and serological autoantibody tests before lip gland biopsy may reduce invasive examinations for patients without significantly increasing the rate of missed diagnosis. According to imaging and serological autoantibody tests, SS can be categorized into early, active, and quiescent stages.